DETERMINING THE AMOUNT OF TEMPEH PRODUCTION BASED ON DEMAND AND INVENTORY DATA USING FUZZY LOGIC METHOD (CASE STUDY: “MURNI” SOYBEAN TEMPE MSMEs MADIUN) - Nazwa Khairunnisa; Muhammad Faiz Assariy; Daffa Zulqisthi; Muhammad Raihan Prasetya; Kanaya Fatimah Madania; Holy Nurani Rabbina; Rifki Oktavia; Siti Hasna Raihana; Astrid Virta Ayu Alzahra; Chika Hayya Sabillah (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
Tempeh is a typical Indonesian food that is consumed by almost all people. In the industrial world, companies are required to increase productivity because many competitors are increasingly competitive. The increase in raw material prices makes companies reluctant to buy materials in large quantities, so companies tend to maintain stock or supply of materials in order to meet increasing demand. This research aims to estimate the amount of tempe production using the Mamdani fuzzy logic approach with consideration factors in the form of supply and consumer demand. The research method uses literature reviews, testing with Matlab, and manual calculations to analyze demand and supply of tempeh in the industry. The test results using Matlab and manual calculations on tempe demand and supply obtained data that is in accordance with existing history, where if there is a demand for 6006 units of tempeh with a raw material supply of 6945, then it is predicted that the company will produce 6569 units of tempeh. It is hoped that this research can help the tempe industry in preparing production plans.